Transport development and poverty reduction in Northeast Brazil - BENEVENUTO, RODOLFO GOMES (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2020)
The recent shift in focus from the income-based to the multidimensional understanding of poverty has revealed that the global goal of ending poverty requires more than isolated and remedial actions. Integrated efforts from scholars and practitioners across the range of human knowledge are rather necessary to meet the agenda of leaving no one behind and uplift over 700 million people out of extreme poverty. This thesis examines the key contributions that transportation development can promote to alleviate several dimensions of exclusion and the structures underpinning the intergenerational poverty transfer. The particular challenges and research gaps on this theme in the context of Northeast Brazil are addressed throughout this research. While the transport-poverty nexus has long been explored in the academic literature of wealthier and more urbanised regions, this thesis sets out theoretical frameworks and practical tools that are applicable to regions where poverty is widely and severely spread. The research developed in this thesis delves into the transportation and poverty literature from three distinct perspectives: theoretical (i.e. links between transport and poverty in the Global South), ex-post (i.e. social outcomes of transport experiences) and ex-ante (socially inclusive transport planning). A transport policy analysis framework showing the various dimensions of transport-related exclusion present in the Global South is initially proposed with reference to the literature. To illustrate the links between transport and poverty, the accessibility to healthcare and urban centres of nearly half-million low-income families from rural Northeast Brazil is statistically and spatially evaluated. This first set of findings show that 53.5% of them are living farther than 5 km from the nearest primary care centre and over 49% are at a distance greater than 10km from the closest urban centre, where majority of the essential services are located. Meanwhile, from the ex-post perspective, a quasi-experimental analysis is developed particularly tailored to the Northeast Brazil, drawing on open access data only. Whilst the results suggest a wide range of positive social effects that are associated with recent transport infrastructure investments in Northeast Brazil, they also point out to negative outcomes of these interventions upon the average income of people living in extreme poverty. This fact emphasises the necessity for ex-ante assessments of the social dimension and the distributional impacts of transport interventions. Finally, extensive work was subsequently conducted to develop a spatial accessibility poverty index that could be fed into a comprehensive screening framework of transport needs. This final ex-ante approach draws upon the theoretical framework initially proposed to shed light on how inclusive transportation can be objectively planned to tackle the poverty cycles more effectively. The results point out to priority lines of actions derived from a hierarchisation of the transport-related exclusion dimensions that can help guide targeted transport initiatives at the local and regional level. Findings call attention to several sub-regions in Northeast Brazil that are affected by multiple hotspots of transport-related exclusion and, thus, should be prioritised by future transport interventions. In summary, the exploratory nature of this thesis raises evidence that can be a valuable input to highlight the essential role that transport academics and practitioners ought to play in order to stand up to poverty when developing new transport policies.
APPROVED
Keywords: poverty; Global South; Brazil; accessibility; ex-ante; ex-post; transport